Analysis of Business Ethics Among Food Micro, Small, and Medium Enterprises from a Sharia Perspective - Sumayyah Nanda Alfiani; Ginan Wibawa; Muhammad Saepul Ulum (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study is motivated by the gap between the normative concepts of Islamic business ethics in fiqh muamalah and their empirical implementation at the level of Micro, Small, and Medium Enterprises, particularly in the food sector, which is characterized by high economic dynamics. In practice, not all business actors are able to consistently implement Sharia values due to market pressures and limited resources. Therefore, this study aims to analyze the implementation of Sharia-based trading ethics, assess its conformity with the principles of muamalah, and identify the factors influencing the economic behavior of Micro, Small, and Medium Enterprise actors on Jalan Sindang Sari, Cileunyi Wetan. This research employs a qualitative approach using a case study strategy. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The findings indicate that most Micro, Small, and Medium Enterprise actors have implemented the principles of honesty (shiddiq), transparency (tabligh), responsibility (amanah), and price fairness based on market standards, although variations remain in the transparency of raw material information. These findings affirm that Sharia business ethics are not merely normative but also function as social capital in fostering trust and business sustainability. The implication is the need to strengthen Sharia economic literacy and standardize product transparency to improve the quality of business practices among Micro, Small, and Medium Enterprises.